Nicotinamide: A cardioprotective form of Vitamin B3 - Du, Qingyou (Archives of Pharmacy, 2024)
Nicotinamide, a form of vitamin B3, has emerged as a potential cardioprotective agent against ischemia-reperfusion (I/R) injury, a critical factor in the pathogenesis of myocardial infarction, heart failure, and other cardiovascular diseases. This compound plays a significant role in energy metabolism, DNA repair, and cell survival by participating in the biosynthesis of NAD+, a coenzyme essential in redox reactions. The underlying mechanism of cardioprotection afforded by nicotinamide involves enhancing NAD+ biosynthesis, which in turn regulates SUR2A to modulate ATP-sensitive K+ (KATP) channels, influences sirtuin activity, and affects poly(ADP-ribose) polymerases (PARPs) activity to conserve NAD+ levels. Additionally, nicotinamide exhibits anti-inflammatory properties, regulates autophagy, and exerts antioxidant effects, collectively contributing to its potential to mitigate the impact of I/R injury on the myocardium. Despite its wide range of therapeutic applications and safety profile, distinctions between nicotinamide and another form of vitamin B3 nicotinic acid (niacin) are crucial, especially regarding their effects on lipid profiles and vascular functions. Unlike niacin, nicotinamide does not affect lipid levels or pose a risk of increasing cardiovascular events, highlighting its safety for clinical use at recommended doses. However, so far, no clinical study of nicotinamide in the context of cardioprotection has been done. Randomized controlled trials are clearly needed to examine nicotinamide’s possible role in clinical practice, define optimal dosing strategies, and understand its long-term effects. However, considering the history of nicotinamide use, this is a compound that could be quickly introduced in clinical practice for cardioprotection.